2004
DOI: 10.1152/ajpheart.00575.2003
|View full text |Cite
|
Sign up to set email alerts
|

Transmural left ventricular mechanics underlying torsional recoil during relaxation

Abstract: Early relaxation in the cardiac cycle is characterized by rapid torsional recoil of the left ventricular (LV) wall. To elucidate the contribution of the transmural arrangement of the myofiber to relaxation, we determined the time course of three-dimensional fiber-sheet strains in the anterior wall of five adult mongrel dogs in vivo during early relaxation with biplane cineangiography (125 Hz) of implanted transmural markers. Fiber-sheet strains were found from transmural fiber and sheet orientations directly m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
146
1
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(152 citation statements)
references
References 46 publications
4
146
1
1
Order By: Relevance
“…These studies established that fiber orientation was a function of transmural location, with fiber direction being predominantly longitudinal in the endocardial region; transitioning into a circumferential direction in the midwall and becoming longitudinal again over the epicardial surface. Myofiber morphology was described either based on orientation of individual fibers or as multiple myocyte 'sheet' arrangements separated by extensive 'sheet cleavage' planes (17)(18)(19)(20). Some investigators depicted the LV as a complex nested continuum where the myofibers entwined to form a mechanical and electrical syncytium (21,22).…”
Section: Myofiber Architecture Of the Left Ventriclementioning
confidence: 99%
“…These studies established that fiber orientation was a function of transmural location, with fiber direction being predominantly longitudinal in the endocardial region; transitioning into a circumferential direction in the midwall and becoming longitudinal again over the epicardial surface. Myofiber morphology was described either based on orientation of individual fibers or as multiple myocyte 'sheet' arrangements separated by extensive 'sheet cleavage' planes (17)(18)(19)(20). Some investigators depicted the LV as a complex nested continuum where the myofibers entwined to form a mechanical and electrical syncytium (21,22).…”
Section: Myofiber Architecture Of the Left Ventriclementioning
confidence: 99%
“…101 Measuring longitudinal or circumferential shear is another promising approach to the assessment of torsion with speckle tracking, allowing full assessment of overall deformation in addition to three-dimensional strains and investigation of regional differences in torsion. 102 Hypertension, like other progressive myocardial diseases for example, coronary artery disease and hypertrophic cardiomyopathy, preferentially affects subendocardial function and the longitudinal fibres running along it. 103 The epicardial function may remain relatively unaffected.…”
Section: 66mentioning
confidence: 99%
“…When data from seven hearts were combined, a bimodal distribution of angles was found with two distinct orientations of the cardiac laminar structure lying on average at 45.5 • and 117.6 • [29]. These findings are backed by histological studies [1,2,11,16,19,27,67] that have also identified two distinct populations of sheets in combined data that correlate well with the DTI measurements. Our measured sheet angles for lateral sectors show large intra-and interheart variability, particularly in basal regions (see Figs.…”
Section: Sheet Structurementioning
confidence: 54%
“…The data presented here also offer some possible explanations for the differences in the histologically-derived descriptions of sheet morphology in the literature. Some reports [11,46] describe a single population of sheets that bend through the cardiac wall, while others describe dual populations [1,2,11,16,19,27,67]. Gross variation in sheet structure between individual hearts will result in differing reports, as will local variation in sheet orientation associated with the precise positioning of the regions selected for characterisation.…”
Section: Sheet Structurementioning
confidence: 99%